Carbon-Based Nanoadsorbents for the Removal of Emerging Pollutants - M. Venkata Ratnam; P. Akilamudhan; K. Senthil Kumar; S. Narasimha Reddy; K. Nagamalleswara Rao; Feroz Shaik; D. M. Reddy Prasad (Adsorption Science & Technology)
Emerging contaminants (ECs) are substances that have been detected in water but have not been thoroughly tested or regulated. Pesticides, cosmetics, pharmaceuticals, and other medications are examples of compounds in this category. Even at low quantities, these pollutants can harm human health and the environment; therefore, avoiding them is critical. The consequences of EC pollution on the endocrine, hormonal, and genetic systems are causing significant concern. Even with current best practices and available technology, it is difficult to totally eliminate ECs from municipal and industrial wastewater treatment plants. Adsorption has been the method of choice for EC removal since it is less costly, more effective, and easier to use. To treat ECs, newer generation nanoadsorbents are employed. Adsorption was greatly enhanced by functional changes to the adsorbent surface. Carbon nanostructures are widely used as adsorbents because of their outstanding surface properties, adaptability, large surface area, adjustable structural changes, and high chemical stability. This review reviews and examines recent research on the production and use of carbon-based nanoadsorbents. The emphasis is on carbon nanotubes, graphene, and graphene-derived adsorbents. It is being investigated if these adsorbents can be used to extract hormone-disrupting chemicals and other emerging pollutants. The sources and classification of these pollutants, treatment knowledge gaps, and novel prospects for increasing carbonaceous nanoadsorbent utilization were all explored. The environmental and health problems associated with EC use are also studied.